The Relationship between Formal and Informal Care among Adult Medicaid Personal Care Services Recipients - McMaughan Moudouni, Darcy K (Blackwell Science Inc, 2012)
OBJECTIVES: To test hypotheses concerning the relationship between formal and informal care and to estimate the impact of hours of formal care authorized for Medicaid Personal Care Services (PCS) on the utilization of informal care. DATA SOURCES/STUDY SETTING: Data included home care use and adult Medicaid beneficiary characteristics from assessments of PCS need in four Medicaid administrative areas in Texas. STUDY DESIGN: Cross-sectional design using ordinary least-squares (OLS) and instrumental variable (IV) methods. DATA COLLECTION/EXTRACTION METHODS: The study database consisted of assessment data on 471 adults receiving Medicaid PCS from 2004 to 2006. PRINCIPAL FINDINGS: Both OLS and IV estimates of the impact of formal care on informal care indicated no statistically significant relationship. The impact of formal care authorized on informal care utilization was less important than the influence of beneficiary need and caregiver availability. Living with a potential informal caregiver dramatically increased the hours of informal care utilized by Medicaid PCS beneficiaries. CONCLUSIONS: More formal home care hours were not associated with fewer informal home care hours. These results imply that policies that decrease the availability of formal home care for Medicaid PCS beneficiaries will not be offset by an increase in the provision of informal care and may result in unmet care needs.